Representación social de la muerte en un grupo de médicos - Antonio Rodríguez Sánchez (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2022)
Introduction: In the relationship of physicians with death in the scene of struggle that is the hospital, inter and intrasubjective processes are manifested that legimitize their role behaviors. Objective: Characterize the social representation of death in a group of physicians from a clinical-surgical hospital in Havana. Method: Mixed, explanatory and cross-sectional research carried out between June and September 2019 in a non-probabilistic simple of 35 physicians. In the quantitative stage, the Free association of words was applied and for the Qualitative stage, the semi-structured interview Results: The central nucleus is made up of the Affective Impact (FR= 60; M= 3.5) category; while the contents of the peripheral system that are closest to the nucleus in structural order are the categories Rational Conception (FR=20; M= 2.8) and Post-mortem State (FR= 22; M= 4.4). Discussion: The social representation of death is characterized by having a central nucleus that reflects the diversity of emotions that are experienced. While the peripheral system accounts for the cognitive aspects that are used for a conception of death and that are organized around biological rationality. This in the context of the characteristics of the Dying Process Scenario with which they related.